PENGEMBANGAN PERANGKAT PEMBELAJARAN IPA BIOLOGI BERBASIS MODEL PEMBELAJARAN PEMAKNAAN DALAM PEMBELAJARAN IPA DAN PENUMBUHAN SENSITIVITAS MORAL - Putra, IrwanSyah; Ibrahim, Muslimin; Supardi, Z.A. Imam (Universitas Negeri Surabaya, 2014)
This research aims to develop devices based science learning biology teaching model in an effort to teach the meaning of science and foster moral sensitivity on the subject of human respiratory system. This study was classified as research development , ie developing syllabus , lesson plans , worksheets , BAS , and THB . Follow the development of the design of the 4- D models of Thiagarajan (1974 ) followed by the implementation phase of learning in the classroom using a pretest - posttest design. Device developed then validated by experts and tested first at 10 eighth grade students of SMP Negeri 1 Tarik. The results showed the validity of the RPP , BAS , and worksheets categorized very well , and the validity of test questions categorized invalid and valid enough. Readability level device includes worksheets for BAS and 77,2 % to the category of material is too easy , and a description of the difficulties include BAS and LKS was 22,1 % with a fairly easy category . The success of RPP during three meetings very well categorized ; activity levels of students categorized quite active ; better student learning outcomes tests of cognitive abilities , processes , psychomotor and moral sensitivity tests considered complete . Barriers in the PBM especially low student motivation in participating in learning .Based on the analysis of data, it can be concluded that the biology-based science learning learning model of meaning on the subject of the human respiratory system is able to teach science and junior high school students growing moral sensitivity. Penelitian ini bertujuan mengembangkan perangkat pembelajaran IPA Biologi berbasis model pembelajaran pemaknaan sebagai upaya mengajarkan IPA dan menumbuhkan sensitivitas moral pada pokok bahasan Sistem Pernapasan Manusia. Penelitian initergolong penelitian pengembangan, yaitu mengembangkan Silabus, RPP, LKS, BAS, dan THB. Pengembangan perangkat mengikuti rancangan 4-D model dari Thiagarajan (1974) dilanjutkan dengan tahap pelaksanaan pembelajaran di kelas menggunakan rancangan pretest-posttest design. Perangkat yang dikembangkan kemudian divalidasi oleh pakar dan diuji coba I pada 10 siswa kelas VIII SMP Negeri 1 Tarik. Hasil penelitian menunjukkan validitas RPP, BAS, dan LKS berkategori baik; dan validitas soal tes berkategori valid. Tingkat keterbacaan perangkat meliputi BAS dan LKS sebesar 77,2% dengan kategori materi mudah; dan deskripsi kesulitan perangkat meliputi BAS dan LKS sebesar 22,1% dengan kategori tidak sulit. Keterlaksanaan RPP selama tiga kali pertemuan berkategori sangat baik; tingkat aktivitas siswa berkategori cukup aktif; hasil tes belajar siswa baik kemampuan kognitif, proses, psikomotor dan tes sensitivitas moral berhasil melampaui KKM yang ditetapkan. Hambatan dalam PBM terutama siswa belum terbiasa dengan model pembelajaran pemaknaan. Berdasarkan hasil analisis data, dapat disimpulkan bahwa perangkat pembelajaran IPA Biologi berbasis model pembelajaran pemaknaan pada pokok bahasan sistem pernapasan manusia efektif membelajarkan IPA dan menumbuhkan sensitivitas moral siswa SMP.